MODERN ASPECTS OF KNEE JOINTS DEGENERATIVE-DYSTROPHIC LESIONS PATHOGENESIS AS A BASIS FOR CONSERVATIVE TREATMENT - Pidvalnyuk, V.V.; Zolotaryova, N.A.; Shepitko, K.V.; Dzygal, O.F.; Lapshin, D.Ye.; Vastianov, M.R. (World of Medicine and Biology, 2025)
The purpose of the study was to provide a comprehensive overview of the pathophysiological mechanisms underlying degenerative-dystrophic joint damage and to identify therapeutic approaches to improve joint function and intra-articular cartilage nutrition. This review examines the current etiological factors and pathophysiological mechanisms of degenerative-dystrophic and inflammatory lesions of the large joints of the lower limbs, with a view to explaining the rationale for the use of prolotherapy with hypertonic glucose and/or dextrose solutions. A systematic analysis of studies from 2020 to 2025, drawn from the medical databases PubMed, Google Scholar, Web of Science, and SCOPUS, demonstrates the complexity and cascade of osteoarthrosis pathophysiological mechanisms, which significantly complicate the clinical manifestations of the disease and render drug therapy ineffective. The authors focus on prolotherapy, a regenerative medicine technique that uses hypertonic glucose and/or dextrose solutions, injected into damaged areas of the knee joint, to relieve chronic pain and stimulate the natural regeneration of intra-articular tissues. Clinical data confirms prolotherapy’s efficacy in reducing pain and improving joint mobility, often achieving better results than traditional treatments. In their conclusion, the authors emphasize the alternative importance of prolotherapy for patients with gonarthrosis who are looking for non-invasive treatment options.